2020
DOI: 10.7189/jogh.10.011007
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of COVID-19 among income-poor households in the Philippines: A cross-sectional study

Abstract: BackgroundThe presence of COVID-19 in low-and middle-income countries (LMICs) is raising important concerns about effective pandemic response and preparedness in the context of fragile health systems and the pervasiveness of misinformation. The objective of this study was to gain an understanding of how COVID-19 was perceived by households experiencing extreme poverty in the Philippines. MethodsThis study was conducted in partnership with International Care Ministries (ICM), a Philippine-based non-governmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

50
243
10
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(318 citation statements)
references
References 34 publications
50
243
10
15
Order By: Relevance
“…17 Furthermore, 47.8% practiced proper hand washing and only 25.6% avoided mass gatherings in the weeks before. This finding was much lower than studies in Ethiopia, 6,18 the Philippines 9 and Malaysia. 29 This may be due to the difference in the level of education, age group, information seeking behavior and access to information which could affect the level of practice.…”
contrasting
confidence: 70%
See 1 more Smart Citation
“…17 Furthermore, 47.8% practiced proper hand washing and only 25.6% avoided mass gatherings in the weeks before. This finding was much lower than studies in Ethiopia, 6,18 the Philippines 9 and Malaysia. 29 This may be due to the difference in the level of education, age group, information seeking behavior and access to information which could affect the level of practice.…”
contrasting
confidence: 70%
“…The response to the COVID-19 pandemic has exposed that basic disease prevention and control systems are insufficient in terms of human resources and laboratory testing capacity. 9 Being the most populous African nation, Ethiopia could certainly be associated with a higher risk of increased morbidity and mortality due to COVID-19. Thus, there is a need to examine knowledge, attitudes and practice, and associated factors towards the COVID-19 pandemic especially for religious clerics and traditional healers (THs).…”
Section: Introductionmentioning
confidence: 99%
“…One nal parameter we looked at regarding knowledge and practices towards COVID-19 was the attitude parameter of how worried our participants were about getting infected. Indeed, we found that being worried about the possibility of being infected with the COVID-19 causing virus does signi cantly associate with higher knowledge and better practices as has been found elsewhere [27].…”
Section: Discussionsupporting
confidence: 73%
“…It is implied that changing public behaviors and attitudes for COVID-19 prevention would require the promotion of knowledge, and if needed, correction of inaccurate and misguided information. Knowledge as a fundamental predictor of health behaviors has been validated in many public health areas [27,31,32]. We also stress that attention must be paid to those who showed particularly low COVID-19 knowledge, as they are less likely to perform preventive behaviors.…”
Section: Discussionmentioning
confidence: 90%
“…Behavioral factors toward COVID-19 are also unevenly distributed among people [26]. One study revealed that males, less educated individuals, and elders showed lower levels of COVID-19 knowledge and behaviors compared to their counterparts [27], and another study found that risk perception differed by one's social support [6]. Another study on Chinese undergraduate students revealed that gender, major and school styles affect student's attitude and practice [28].…”
Section: Introductionmentioning
confidence: 99%